Acerca de los intensificadores vaya y qué: un estudio comparativo. - Tanghe, Sanne (Bulletin of Hispanic Studies (1475-3839), 2013)
In European Spanish the interjection "vaya" may function as an intensifier of nominal phrases and, thus, shows a behaviour similar to that of the exclamative quantifier "qué" functioning as an intensifier. This contribution proposes an empirical and comparative analysis between the syntactic and pragmatic behaviour of the intensifiers "vaya" and "qué." In the first place, the study exposes the fact that "vaya," as opposed to "qué," may be external to the syntactic structure of the intensified phrase and that the noun intensified by "vaya" prefers carrying a relative clause over functioning as an argument. Moreover, the speaker prefers the use of "vaya" in a depreciative context. At the same time, concerning the syntactic characteristics, a diachronic study shows that especially since the 1960s "vaya" demonstrates a behaviour increasingly more similar to that of the intensifier "qué."